Competence Development Of Sharia Banking Employees In Supporting Career Path - Heny Yuningrum; Zaenuri Zaenuri; Mochamad Toriq Rasyal Aditya Saputra (Universitas Islam Negeri (UIN) Walisongo Semarang, 2022)
AbstractPurpose - The purpose of this research is to provide accurate information on what skills are needed by a banking employee in the world of work and what training is needed to enhance their career.Method - This research uses a type of qualitative research with a descriptive approach. And the techniques used are survey techniques, case studies, comparative studies, studies of time and motion spans, behavior analysis, and documentary analysis.Result - To develop the competence of serving candidates, especially students, is really needed to survive the competition workplace in this current era of digitalization. The Universities must be able to discuss and find the information from the stakeholders in this case is sharia banking. The letter of degree or bachelor only supports the competence not the main to work. The result of the Forum Discussion Group (FGD) is that the curriculum must have Management knowledge, Leadership, Teamwork and Skills. While that skill was include Content writing, Business analysis, Analytical reasoning, Digital marketing, Cloud computing, Critical thinking. And the strategy to develop student competence is beauty class training, teamwork training, performance grooming training, compute training, account training and graphic design training.Implication - This research can be a recommendation to educational institutions or universities and even financial institutions themselves to improve the skills of their employees or when recruiting new employees.Originality- Employee competency development can be used by banking institutions or educational institutions to improve the skills of their employees in facing the current digitalization era.